Turkish Scales Used In Assessing Health Literacy - Ceylan, Okan (Turkey Health Literacy Journal, 2020)
As knowledge about illness and medical science has extendend among years, health literacy, which is the ability of the patient to understand, interprete the medical information and act appropriately according to this ability, became more important for people to sustain their healthy living. Due to health promotion dictionary which was published in 2011 health literacy is aiming to promote personel and community health by encouraging people to take action in changing the life sytle and community health with the increase in information, attitude and reliance of people. After the feed back evaluation of health materails, a tool for evaluating the health litercy tought to be essential so the first health literacy assessing tool National Assesment of Adult Literacy was developed. In time many assessing tools have been developed and the number of tools is increasing. ideal assessment should be short, simply applicable and reliable. Many health literacy assessing tools that have been developed in foreign languages were translated to Turkish. Also there are many scaling tools that have been developed in Turkish.
Keywords: Pandemic; Covid-19; Transmission Chain; Health Literacy